Gender and early learning environments - Irby, Beverly J.; Brown, Genevieve (Research on women and education., 2011)
The Research on Women and Education SIG of the American Educational Research Association presents the third book in its series, Gender and Early Learning Environments. Finding after the publication of Gender and Schooling in the Early Years, the second book in the series, that there was and is a paucity of published literature on early childhood gender issues, the editors determined that one additional book on early childhood and gender issues was warranted in this series. The latest book in the series, Gender and Early Learning Environments, is encompassing of a wide range of topics addressing early childhood influences on gender and development of the whole child. For early childhood educators, this book aides in making visible and exploring the definition of what gender means in contemporary culture.